POLICY IMPLEMENTATION OF THE NATIONAL ACTION PLAN FOR THE PREVENTION, ERADICATION, ABUSE AND ILLICIT DRUG TRAFFICKING (P4GN): TOWARDS STRENGTHENING NATIONAL RESILIENCE - Clarissa Ivana Kartika Dinansi; Dhiana Puspitawati; Alfi Haris Wanto (Faculty of Social and Political Sciences, Universitas Diponegoro, 2024)
The high level of drug abuse that threatens social stability and national security is the background of this research. The urgency of the research lies in the need for cross-sector policy synergy to effectively tackle drug trafficking. This research aims to analyze the implementation of the prevention, eradication, abuse and illicit drug trafficking (P4GN) policy. This research uses a qualitative method with a descriptive-analytical approach, combining literature studies and in-depth interviews with relevant policy stakeholders. The results show positive impacts of the policy such as increased public awareness through the Drug Information Education Center (PIE), although there are still obstacles such as weak coordination between agencies and limited resources. Law enforcement by BNN and Polri shows significant progress, but needs to be balanced with strengthening rehabilitation programs for addicts. Implementation of this policy requires periodic evaluation, development of anti-drug module-based education, and community empowerment to strengthen overall national resilience.